Analysis of Online Classes in Physical Education during the COVID-19 Pandemic - Jieun Yu; Yongseok Jee (MDPI AG, 2020)
Background and objectives: This study analyzed the effectiveness of the online practical classes (OPC) in physical education (PE) in compliance with the ADDIE model during the COVID-19 pandemic. Materials and Methods: Participants had no prior experience in OPC and total 75 participants were enrolled in this study. This study selected 15 universities in consideration of regional equality and randomly selected two professors and three students from each university. Results: (1) The learning interventions were not feasible for team projects. (2) In the implementation phase, most learners felt that errors persisted. (3) In the evaluation phase, educators reported unenthusiastic involvement of students and the learners were merely submitting assignments. (4) An appropriate level of the effectiveness through OPC showed significantly different between educators and learners. Conclusions: The findings indicate that timely and quality feedback should be provided for the successful execution of OPC in PE; the educators should prepare ahead and reduce technical errors and motivate learners continuously. Lastly, to prepare for the new normal after COVID-19, universities should provide enough time for educators to make OPC-videos and teach students in real time to ensure consistent feedback.